An unexpected visitor: brown pelicans (Pelecanus occidentalis) and their interactions with artisanal fishermen in the Anavilhanas National Park (Research, Society and Development, 2022)
The brown pelican (Pelecanus occidentalis) is a seabird with wide geographic distribution along the coast of the American continent. The species lives most of its life at sea, returning to the mainland only to nest. This paper reports the occurrence of brown pelicans in the Anavilhanas National Park, Brazilian Amazon, and describes how artisanal fishermen living in the surroundings of this Conservation Unit have been interacting with this unexpected visitor. Through field sightings and interviews with local residents, up to six brown pelicans were recorded which, according to local residents, appeared for the first time in the second half of 2019. The interactions between fishermen and birds involve especially the offer of fish, but conflicts were also recorded, such as when pelicans are attracted by the smell of fish and head towards fishing vessels, causing fishermen to chase the birds away, and the report of the slaughter of one of the birds for consumption. This is the most interior record of the species in a continental Amazonian environment and the first to describe a cluster of brown pelicans interacting with inhabitants of the region. The results presented demonstrate that we know little about the factors that influence the migration and dispersion of brown pelicans, contribute to a better understanding of cultural attitudes related to human-fauna interactions, and support the conservation management of these rare birds in interior Amazonian areas.